Development of a duplex serological multiplex assay for the simultaneous detection of Epstein-Barr virus IgA and IgG antibodies in nasopharyngeal carcinoma patients - Schieber, Jennifer; Pring, Miranda; Ness, Andy; Liu, Zhiwei; Hsu, Wan-Lun; Brenner, Nicole; Butt, Julia; Waterboer, Tim; Simon, Julia (Cancers, 2023)
Epstein-Barr virus (EBV) IgA and IgG antibodies in serum from nasopharyngeal carcinoma (NPC) patients are well-established markers for EBV-positive NPC. Luminex-based multiplex serology can analyze antibodies to multiple antigens simultaneously; however, the detection of both IgA and IgG antibodies requires separate measurements. Here we describe the development and validation of a novel duplex multiplex serology assay, which can analyze IgA and IgG antibodies against several antigens simultaneously. Secondary antibody/dye combinations, as well as serum dilution factors, were optimized, and 98 NPC cases matched to 142 controls from the Head and Neck 5000 study (HN5000) were assessed and compared to data previously generated in separate IgA and IgG multiplex assays. EBER in situ hybridization (EBER-ISH) data available for 41 tumors was used to calibrate antigen-specific cut-offs using receiver operating characteristic (ROC) analysis with a prespecified specificity of ≥90%. A directly R-Phycoerythrin-labeled IgG antibody in combination with a biotinylated IgA antibody and streptavidin-BV421 reporter conjugate was able to quantify both IgA and IgG antibodies in a duplex reaction in a 1:1000 serum dilution. The combined assessment of IgA and IgG antibodies in NPC cases and controls from the HN5000 study yielded similar sensitivities as the separate IgA and IgG multiplex assays (all > 90%), and the duplex serological multiplex assay was able to unequivocally define the EBV-positive NPC cases (AUC = 1). In conclusion, the simultaneous detection of IgA and IgG antibodies provides an alternative for the separate IgA/IgG antibody quantification and may present a promising approach for larger NPC screening studies in NPC endemic areas.
Gesehen am 04.08.2023